Pre-transplantation Risks and Transplant-Techniques in Haematopoietic Stem Cell Transplantation for Acute Leukaemia. (October 2019) - Gratwohl, Alois; Duarte, Rafael; Snowden, John A.; van Biezen, Anja; Baldomero, Helen; Apperley, Jane; Cornelissen, Jan; Greinix, Hildegard T.; Grath, Eoin Mc; Mohty, Mohamad; Kroeger, Nicolaus; Nagler, Arnon; et al.
Abstract: Background: The role of conditioning intensity and stem cell source on modifying pre-transplantation risk in allogeneic haematopoietic stem cell transplantation (HSCT) is a matter of debate, but crucial when benchmarking centres. Methods: This Retrospective, multicenter exploratory-validation analysis of 9103 patients, (55.5% male, median age 50 years; 1–75 years range) with an allogeneic HSCT between 2010 and 2016 from a matched sibling (N = 8641; 95%) or matched unrelated donor (N = 462; 5%) for acute myeloid (N = 6432; 71%) or acute lymphoblastic (N = 2671; 29%) leukaemia in first complete remission, and reported by 240 centres in 30 countries to the benchmark database of the European Society for Blood and Marrow Transplantation (EBMT) searched for factors associated with use of transplant techniques (standard N = 6375;70% or reduced intensity conditioning N = 2728;30%, respectively bone marrow N = 1945;21% or peripheral blood N = 7158;79% as stem cell source), and their impact on outcome. Findings: Treatment groups differed significantly from baseline population (p < 0.001), and within groups regarding patient-, disease-, donor-, and centre-related pre-transplantation risk factors (p < 0.001); choice of technique did depend on pre-transplantation risk factors and centre (p < 0.001). Probability of overall survival at 5 years decreased systematically and significantly with increasing pre-transplantation risk score (score 2 vs 0/1 HR: 1·2, 95% c.i. [1·1–1·.3], p = 0.002; score 3 vs 0/1 HR: 1·5, 95% c.i. [1·3–1·7], p < 0.001; score 4/5/6 vs 0/1 HR: 1·9, 95% c.i. [1·6–2·2], p < 0.001) with no significant differences between treatment groups (likelihood ratio test on interaction: p = 0.40). Overall survival was significantly associated with selection steps and completeness of information (p < 0.001). Interpretation: Patients' pre-transplantation risk factors determine survival, independent of transplant techniques. Transplant techniques should be regarded as centre policy, not stratification factor in benchmarking. Selection criteria and completeness of data bias outcome. Outcomes may be improved more effectively through better identifying pre-transplantation factors as opposed to refinement of transplant techniques. Funding: The study was funded by EBMT .